La globalización como factor influyente en la identidad cultural de los estudiantes del colegio de bachillerato Ponce Enríquez, periodo 2019-2020 - Sánchez Morocho, Jordy Alexander (My University, 2020)
The purpose of this research is to determine the influencing factors of globalization on cultural identity, to be determined, to have an approach to the social reality in which the students of the Ponce Enrique Baccalaureate school are immersed 2019-2020 period. Globalization is a sociological conception that obeys a process of social construction, whose impact is part of the economy and is dimensioned in a variety of concepts related to the forms of sovereignty in the daily life of the individual, the same that affect the economic context, political, social and cultural. The development of the Tics has been the leading factor in the global scene, being the main cause of the changes of productive systems whose models abide by the virtual dynamics that promote cultural capital, causing acculturation and disarticulation in the social interaction of the individual. The sense of relevance that characterizes the cultural identity of the individual from other nations, states or communities, follows a historical process, where it triggers an ideological connection of appropriation, where cultural characters are expressed in a tangible and intangible way, which have a future tendency modifications produced by the technological development of interconnectivity and telecommunications in the global sphere. The research has a mixed methodological support, so there is the deductive rational epistemological method to obtain the information, which was quantified and analyzed to determine the factors that induce young people to acculturation processes and loss of identity product of the globalization.
La presente investigación tiene como objetivo, determinar los factores influyentes de la globalización sobre la identidad cultural, por consiguiente, tener un acercamiento a la realidad social en la que se encuentran inmersos los estudiantes del colegio de Bachillerato Ponce Enríquez periodo 2019-2020. La globalización es una concepción sociológica que obedece a un proceso de construcción social, cuya repercusión parte desde la economía y se dimensiona en una variedad de conceptos relacionados con las formas de soberanía en la cotidianidad del individuo, las mismas que inciden en el contexto económico, político, social y cultural. El desarrollo de las Tics han sido el factor protagónico en la escena global, siendo la causa principal de los cambios de sistemas productivos cuyos modelos acatan a la dinámica virtual que promueven el capital cultural, ocasionando aculturación y desarticulación en la interacción social del individuo. El sentido de pertinencia que caracteriza la identidad cultural del individuo de otras naciones, estados o comunidades, sigue a un proceso histórico, donde desencadena una connotación ideológica de apropiación, donde ciertos rasgos culturales se expresan de forma tangible e intangible, las cuales poseen tendencia a futuras modificaciones producidas por el desarrollo tecnológico de la interconectividad y las telecomunicaciones en la esfera global. La investigación posee un soporte metodológico mixto, por lo cual se utilizó el método epistemológico racional deductivo para obtener la información, la misma que fue cuantificada y analizada para determinar los factores que inducen a los jóvenes a procesos de aculturación y pérdida de identidad producto de la globalización.
Keywords: IDENTIDAD CULTURAL; GLOBALIZACION; ECONOMIA; SISTEMA PRODUCTIVO